ENGLISH PHONOLOGICAL AWARENESS: A DESCRIPTIVE STUDY OF FIRST GRADE STUDENTS AT AN ELEMENTARY SCHOOL IN NORTHERN BANDUNG - Putri, Nilasari Karinda (2017)
This study aims to investigate first grade students' awareness in English phonology and the factors influencing English phonological awareness. This study employs a mixed method that uses quantitative and qualitative data such as an assessment test, the questionnaire, and the interview as the data collection. The result of the findings indicates that students' performance on English phonological awareness emerges from the sound units in the level of syllable, onset-rime, and phoneme. Factors, for instance the chronological order of language acquisition and language proficiency, have a positive effect towards the performance of students' English phonological awareness. The students may commit a transfer, between the target language and another language previously acquired, that can potentially influence the performance in language development. The reason is because the performance on English phonological awareness is as same as in Indonesian phonological awareness. Some suggestions for future research are proposed based on the findings above.;--- Penelitian ini bertujuan untuk menyelidiki kesadaran murid kelas satu akan fonologi Bahasa Inggris dan faktor-faktor yang mempengaruhi kesadaran fonologi Bahasa Inggris. Penelitian ini menggunakan metode campuran dengan mengambil data kuantitatif dan kualitatif seperti tes penilaian, kuesioner, dan wawancara sebagai kumpulan data. Hasil temuan menunjukkan bahwa kesadaran fonologi Bahasa Inggris murid kelas satu muncul dalam satuan bunyi tingkat suku kata, onset-rime, dan fonem. Faktor-faktor, seperti pemerolehan bahasa secara kronologis dan tingkat kecakapan bahasa, mempengaruhi performa kesadaran fonologi Bahasa Inggris murid kelas satu. Para pelajar mungkin melakukan pemindahan bahasa, antara bahasa yang dituju dan bahasa lain yang sudah dipelajari, yang dapat mempengaruhi performa perkembangan bahasa. Alasan mengapa hal tersebut bisa terjadi karena performa kesadaran fonologi Bahasa Inggris itu sama dengan performa kesadaran fonologi Bahasa Indonesia. Beberapa saran diusulkan untuk penelitian selanjutnya berdasarkan temuan yang ada di penelitian ini.